THE EFFECT OF GAMES-BASED LEARNING MODEL ASSISTED BY QUIZIZZ ON PROBLEM-SOLVING ABILITIES AND MATHEMATICAL UNDERSTANDING OF GRADE V ELEMENTARY SCHOOL STUDENTS - Andri Herdiana; Heris Hendriana; Muhammad Ghiyats Ristiana (Universitas Majalengka, 2026)
This study examines the effect of a Game Based Learning (GBL) model assisted by Quizizz on mathematical problem-solving ability and mathematical understanding of fifth-grade elementary school students, and exploring their learning experiences. A sequential explanatory mixed methods design was used with 70 fifth-grade students and one teacher at SDN Soreang in the second semester of 2025/2026. Data were collected through tests, open-ended questionnaires, interviews, observations, and documentation. Quantitative data were analyzed using Shapiro-Wilk normality test, Mann-Whitney U test, and N-Gain; qualitative data through reduction, categorization, and thematic analysis. Mann-Whitney U results showed significant differences in both variables (Sig. = 0.000 < 0.05). The experimental group achieved N-Gain of 56.11% (moderate) for problem-solving and 56.55% for mathematical understanding, far exceeding the control group (21.81% and 29.64%). GBL with Quizizz more effectively supports procedural engagement than deep conceptual reasoning. Student responses averaged 74% (good category). GBL needs supplementing with conceptual guiding questions and reflective activities to fully optimize mathematical understanding.